Preimplantation genetic testing legislation and accessibility in the Nordic countries. (10th March 2020) - Hreinsson, Julius; Lundin, Kersti; Iwarsson, Erik; Hausken, Jon; Einarsson, Snorri; Grøndahl, Marie Louise; Hydén‐Granskog, Christel; Ingerslev, Hans Jakob
Abstract: Introduction: Assisted reproduction technologies are being rapidly developed and implementation of preimplantation genetic testing (PGT) has allowed patients with genetic disorders to initiate pregnancies while minimizing or eliminating the risk of transmitting these disorders to their offspring. Testing for numeric chromosomal anomalies has been proposed as a way to increase efficacy in assisted reproduction; however, this remains disputed. Legislation is lagging behind the rapid developments in this field. Material and methods: We conducted a structured online survey of legislation and accessibility to preimplantation genetic testing in the Nordic countries to compare the regulation and uptake of this technique. The survey was designed and answered by the authors. Results: Key elements in the regulation of preimplantation testing for monogenic disorders and structural rearrangements are similar in the Nordic countries, although accessibility varies since only Denmark, Finland, and Sweden have national clinics offering treatment. In addition, Denmark and Finland have private clinics offering PGT. Regulation is the most stringent in Norway where a national board evaluates all couples seeking treatment. Treatment volumes vary between the Nordic countries, with Norway and Finland having lowest treatment numbers. Preimplantation genetic testing for aneuploidy in the embryo varies between the Nordic countries: Finland and Iceland allow this form of treatment, Denmark and Sweden offer it only in the form of a research protocol, and Norway does not allow it at all. Therefore the number of treatment cycles involving testing for embryo aneuploidy are lower in the Nordic countries than in other countries where this treatment option is more common. Conclusions: Science needs to inform politics regarding the rapidly evolving field of reproductive medicine and we recommend harmonization of legislation and accessibility between the Nordic countries.